Instability in turmeric (Curcuma Zonga L.) production in India - SANKARAN, N AJITH KUMAR, P G (Journal of Spices and Aromatic Crops, 1998)
The factors responsible for the instability in turmeric (Curcuma longa) production in India were studied. Instability analysis showed that yield instability increased marginally in the eighties. However, the decrease in area instability more than compensated for the increase in yield instablitity resulting in reduction of production instability. Decomposition analysis showed that yield instability was the dominant factor affecting production instability. Therefore future development programmes should envisage stabilisation of yield which will stabilise production. The yield instability could be reduced by investing on research towards evolving of cultivars suitable for existing agroclimatic conditions.